KINETIKA NITRAT DI DALAM TANAH PADA APLIKASI VERMIKOMPOS - Kartika Utami; Evi Intan R.S.; Zainal Muktamar; Yudhy Harini Bertham; Kanang S. Hindarto (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2023)
Nitrogen is the most often deficient in the soil and will be impacted by farmers associated with the economic issue. Nitrogen exists in soil systems in many forms and changes, such as mineralization and mobilization, nitrification, denitrification, volatilization, runoff and erosion, and leaching. The Inceptisol has a pH of 5,5 (acid), impacting soil nutrients such as nitrogen, phosphor, potassium, and organic-C; meanwhile, Ultisols have high acidity and Al exchangeability. This study aimed to determine the rate of nitrate availability on Ultisols and Inceptisols added dairy cattle waste vermicompost. The experiment was arranged by Randomized Completely Design with two factors. The first factor was vermicompost with three doses; there were 0 ton/h, 15 tosn/ha, and 30 tons/ha and the second factor was two types of soils, Inceptisol and Ultisol. The experiment was conducted by three times. The result is on the R2 value, the reaction order kinetics model, which best explains the relationship between vermicompost dosing and nitrate availability in Ultisols and Inceptisols, is a first-order equation. The constant nitrification rate was 0.04 to 0.06 daily with three dairy cattle waste vermicompost dose levels. The potential nitrification showed that a high-level dose increased high nitrate. In Ultisols, the nitrification potential has risen from 1.21 to 1.44 mg/kg NO3-  in others, increasing from 1.36 to 1.41 mg/kg NO3-. Dairy cattle waste vermicompost can accelerate nitrification in acidic soil, especially Ultisols and Inceptisols. This biofertilizer can supply nitrate to the soil by enhancing microbial activity. Nitrate availability in the soil can be supported by 30 tons ha-1 dairy cattle waste vermicompost.